Some properties of thin film structures on the base of ZnO obtained by MOCVD method - Roshchina, N. M.; Smertenko, P. S.; Stepanov, V. G.; Zavyalova, L. V.; Lytvyn, O. S. (Видавництво Львівської політехніки, 2012)
This paper reports on the ZnO film structures obtained by MOCVD method on Si substrates. The phase composition, structure and morphology of ZnO films as well as electrophysical properties of ZnO/Si heterojunction on their base were investigated. The possible charge flow mechanisms in ZnO/Si heterojunction are discussed.
Keywords: ZnO/Si heterojunction; metaloorganic chemical vapour deposition; current–voltage characteristics